A Key Performance Indicator for an Integrated Assessment of the Social Sustainability of an Enterprise - DEMIAN, Mihai; GRECU, Luminita; DEMIAN, Gabriela (European Journal of Sustainable Development, 2025)
This paper proposes a tool for the integrated assessment of a company's social sustainability. This tool is an integrated indicator, composed of two partial indicators, which refer to two different aspects of social sustainability: the impact of the company's activity on employees, its relationship with customers and the local community. To develop this tool, 34 criteria were formulated, as well as ways to quantify the company's responses to them. The criteria were grouped into several categories, depending on the aspects to which each refers. Based on each group, two partial indicators are constructed: one indicator relating to the working conditions of employees and the other indicator relating to the relationship with customers and society. For the company's responses to these criteria, formulas were proposed that lead to normalized values, which allowed them to become comparable and aggregated for the construction of the indicator. The indicator proposed in the paper can be used to monitor progress and results related to social sustainability, as well as to rank companies that aim to achieve sustainable development objectives. Keywords: measure social sustainability; quantifying responses; key performance indicator; key performance indicator; sustainable development.